Level of Knowledge, Attitude, and Behavior of Students at SMA Negeri 13 Medan on Prevention of Sexually Transmitted Infections - Elisabeth; Maria Magdalena Simatupang; Delfitri Munir; Olga Rasiyanti Siregar (Talenta Publisher, 2024)
Background: Sexually Transmitted Infection (STI) is a contagious disease that has been a health problem around people all over the world because the incidence rate of sexually transmitted diseases (STDs) tends to increase. Objective: This research objects to know the level of knowledge, attitudes and behavior of SMA Negeri 13 Medan students regarding STI prevention. Methods: This is descriptive research with cross-sectional design. The sampling technique is done by stratified random sampling with questionnaire as data collection tool and the data analysis was carried out using descriptive statistics. Results: The results showed that the knowledge level of SMA Negeri 13 Medan students about preventing STI was mostly in the good category (54.2%), attitudes were in the good category (93.7%), and behaviors were in the moderate category (47.9%). Conclusion: Most of students have a good knowledge level, good attitude level, and moderate behavior level towards STI prevention.